2016
DOI: 10.1111/lic3.12318
|View full text |Cite
|
Sign up to set email alerts
|

The History of Emotions and Middle English Literature

Abstract: Critics have long addressed questions of affect, feeling and emotional expression in Middle English literature, but only in recent years has their interest begun to take theoretical form under the rubric of the ‘history of emotions’. Current critical attitudes to the study of emotions in the past have been shaped substantially by the work of historians, whose focus on emotion in documentary sources has been influenced in turn by research in the fields of sociology, anthropology, psychology, linguistics and, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, Obermeier et al (2016) stated that although most poems are harder to read than newspapers, such cognitive ambiguity 3 should be expected in poems. Similarly, it has been suggested that ambiguous emotions that impact appreciation are evoked in English poetry (Downes & McNamara, 2016). Based on these observations, in this study, we selected cognitive and emotional ambiguity from the broad concept of ambiguity that is considered important in haiku and poetry and examined how each of these are related to beauty.…”
Section: The Beauty Of Haiku Poetrymentioning
confidence: 98%
“…For example, Obermeier et al (2016) stated that although most poems are harder to read than newspapers, such cognitive ambiguity 3 should be expected in poems. Similarly, it has been suggested that ambiguous emotions that impact appreciation are evoked in English poetry (Downes & McNamara, 2016). Based on these observations, in this study, we selected cognitive and emotional ambiguity from the broad concept of ambiguity that is considered important in haiku and poetry and examined how each of these are related to beauty.…”
Section: The Beauty Of Haiku Poetrymentioning
confidence: 98%
“…Indeed, there was much change amongst the terms for emotion from the Old to the Middle English period: over 2,000 of the Old English terms in this field became obsolete early in the Middle English period and an almost equal number were first recorded during the fourteenth and fifteenth centuries (Diller 2014: 114) 3 . Given the impact of language contact on the development of this lexico-semantic field, there have been recent calls to bring together the findings in the study of historical emotions and medieval multilingualism in order to gain a better understanding of ‘the range of emotional utterance in Middle English texts’ (Downes & McNamara 2016: 451).…”
Section: Focus and Methodological Decisionsmentioning
confidence: 99%
“…3 There are several studies of emotion in Middle English literature; Downes and McNamara (2016) have offered an initiatory exposé on this methodology. In the same journal issue, an article deals with embodied practice in personified emotions (Flannery, 2016) and a whole book has been dedicated to the study of emotions in Arthurian literature (Brandsma, Larrington, Saunders, 2015).…”
Section: This Paper Explores the Different Uses Of Liquidity To Reprementioning
confidence: 99%